PENINGKATAN PERFORMA PERUSAHAAN MELALUI INTEGRASI SUPPLY CHAIN PADA INDUSTRI KECIL DI SEMARANG - Budhi Cahyono (Jurnal Ekonomi dan Bisnis, 2010)
Competition in the future is not company to company, but among supply chain to supply chain.This study based on the fenomena that production process has result very much goods, theproblem about how to deliver goods or services to end customer with optimal and on timedelivery. Company, especially on small businesses must identify their intregration with supplierand customer. The integration concern can be based on customer, supplier, or both. Thisfirst study is to identify the type of integration among the small business. The second studyis to investigat the relationship between integration concern and corporate performance, andfinally the study is designed to understand differences among integration concern. Populationin this study is small businesses Semarang Municipality. Sample for this study are 59 smallbusinesses. Companies were selected by cluster sampling technique. Method of data iscollected by questioner given directly to company and deep interview with the owners. Analyzeused by descriptive analysis and Kruskal Wallis test. The result indicate that almost all the smallbusiness have periphery facing integration. It means that small businesses have integration tosupplier and to customer. The other result of this study indicate that integrate the supply chainhave positive and significant effect on company performance.Keywords: Supply Chain Integration, Company Performance, Small business